The Arrest of the Basilians Atanasie Maxim and Gheorghe Marina in the Attempt to Incriminate the Greek-Catholic Bishop Alexandru Rusu - VIDA-SIMITI, Ionuţ (Studia Universitatis Babeș-Bolyai Historia, 2018)
The present study analyses the beginning of the Communist regime’s offensive against the Romanian Greek-Catholic Church in competition with other Communist states in applying a Soviet pattern of mock trials. For this purpose, the object of the repression authorities at the beginning of 1948 was the staging of a high treason trial to the Metropolitan Bishop unrecognised by the Communist regime of the Romanian Church United with Rome, Greek-Catholic, the Bishop of Maramureș Alexandru Rusu. In order to create a criminal case, the Abbot of the Greek-Catholic Monastery from Bixad, Father Gheorghe Marina, was initially arrested and later was the Provincial Superior of the Order of St. Basil the Great, Atanasie Maxim. The legal indictment has changed many times, because neither with the gross violation of the criminal procedure sufficient rules of evidence could not be provided. Rezumat: Arestarea bazilienilor Atanasie Maxim şi Gheorghe Marina în încercarea de a-l incrimina pe episcopul greco-catolic Alexandru Rusu. Prezentul studiu analizează începutul ofensivei regimului comunist împotriva Bisericii Greco-Catolice din România în concurenţă cu alte state comuniste în aplicarea unui tipar sovietic de procese spectacol. În acest sens, obiectul organelor de represiune la începutul anului 1948 a fost înscenarea unui proces de înaltă trădare Mitropolitul nerecunoscut de regimul comunist al Bisericii Române Unite cu Roma, Greco-Catolică, Episcopul de Maramureş Alexandru Rusu. În scopul creării unui dosar penal a fost arestat iniţial Stareţul Mănăstirii Greco-Catolice Bixad, Părintele Gheorghe Marina, şi ,ulterior, Superiorul Provincial al Ordinului Sf. Vasile cel Mare, Atanasie Maxim. Încadrarea juridică s-a schimnbat de nenumărate ori deoarece nici cu încălcarea grosolană a procedurii penale nu s-a putut constitui un probatoriu suficient. Cuvinte-cheie: călugări bazilieni, Ordinul Sf. Vasile cel Mare, Mănăstirea Bixad, Gheorghe Marina, Atanasie Maxim, Alexandru Rusu, Biserica Greco-Catolică.